Mobile Phone Intimacies and Moral Panics in India - Ravindran, Gopalan (Plaridel Journal of Communication, Media, and Society, 2011)
The rapid proliferation of mobile phones in India has brought along several new cultures to the country's young users of mobile phones. The culture of mobile phone functionalities in their everyday lives requires scholarly attention within the framework of new media modernity. The latter engenders new cultures of intimacies. It also induces moral panics over these new cultures of intimacies. This study demonstrates that the primary and secondary definers of moral panics are gradually scrutinizing the so-called new cultures of young Indians. It further shows that the primary location of the moral panic agent is the family. This is where mobile phones and their users encounter the domesticated dimension of cultural politics of mobile phone intimacies. Finally, this study demonstrates that both the moral panic agents and the young users of mobile phones (a.k.a. "folk devils") use simplistic and stereotypical prisms to address their concerns. Keywords: New Media Modernity, mobile phones, intimacies, moral panics, 'folk devils' and cultural politics